Reduction of Carbon Dioxide in Filtering Facepiece Respirators with an Active-Venting System: A Computational Study - Birgersson, Erik; Tang, Ee Ho; Lee, Wei Liang Jerome; Sak, Kwok Jiang (PLOS ONE, 2015)
During expiration, the carbon dioxide (CO2) levels inside the dead space of a filtering facepiece respirator (FFR) increase significantly above the ambient concentration. To reduce the CO2 concentration inside the dead space, we attach an active lightweight venting system (AVS) comprising a one-way valve, a blower and a battery in a housing to a FFR. The achieved reduction is quantified with a computational-fluid-dynamics model that considers conservation of mass, momentum and the dilute species, CO2, inside the FFR with and without the AVS. The results suggest that the AVS can reduce the CO2 levels inside the dead space at the end of expiration to around 0.4% as compared to a standard FFR, for which the CO2 levels during expiration reach the same concentration as that of the expired alveolar air at around 5%. In particular, during inspiration, the average CO2 volume fraction drops to near-to ambient levels of around 0.08% with the AVS. Overall, the time-averaged CO2 volume fractions inside the dead space for the standard FFR and the one with AVS are around 3% and 0.3% respectively. Further, the ability of the AVS to vent the dead-space air in the form of a jet into the ambient – similar to the jets arising from natural expiration without a FFR – ensures that the expired air is removed and diluted more efficiently than a standard FFR.